Growth of Lactobacillus rhamnosus 64 in whey permeate and study of the effect of mild stresses on survival to spray drying - Lavari, Luisina; Ianniello, Rocco; Paez, Roxana Beatriz; Zotta, Teresa; Cuatrin, Alejandra; Reinheimer, Jorge Alberto; Parente, Eugenio; Vinderola, Celso Gabriel (2018)
In this study, we aimed at optimizing the growth of Lactobacillus rhamnosus 64 in whey permeate supplemented with different ingredients and we also studied the effects of mild stresses on the response to heat and oxidative challenge. Supplementation of diluted whey permeate with yeast extract, tryptone, Tween 80 and Mn–Mg produced ca. 1010 CFU/mL of L. rhamnosus 64 under pH controlled fermentation in anaerobiosis. Cells were exposed to different mild stresses (aerobic: 1 h air 0.3 vol vol−1 min, pH 6, 37 °C); heat (1 h, pH 6, 45 °C, anaerobiosis) and acid (1 h, pH 5, 37 °C, anaerobiosis), followed by heat (55 °C) or oxidative (0.4 mmol/L H2O2) challenge (15 min). Oxidative challenge was more detrimental compared to heat challenge. Anaerobic incubation, cell harvesting at the stationary phase and mild heat stress were more effective for reducing cell death towards heat challenge, whereas cheese whey-starch was effective towards cell protection to spray drying and storage. No effects on cell survival to spray drying were observed when mild stresses were used to increase resistance to spray drying.